Professional Identity Construction: An Inquiry into the Narratives of Indonesian Teachers of English for Young Learners - Hanifia Arlinda; Safrina Noorman; Yanty Wirza (Journal of English Language Studies, 2024)
Teacher professional identity has emerged as a central topic in educational research since the 1990s in light of the increasing understanding of teachers’ roles in different contexts that influence their attitudes, behaviors, and beliefs in teaching (Beijaard, 2019). The identity construction process of English for Young Learners (EYL) teachers in Indonesia needs to be studied more. Employing the narrative inquiry method (Connelly & Clandinin, 1990), this study investigated the process of teacher professional identity construction of four EYL teachers in four different elementary schools in Bandung, Indonesia, and the extent to which the journey affects their beliefs and practice in teaching EYL. I collected the data using semi-structured online interviews, photovoice, and classroom observation. The results suggest that participants' teacher professional identity (TPI) was shaped by experiencing critical events, participating in professional development programs, involving themselves in a community of practice, experiencing teaching practicum, supporting school culture and environment, and teachers' interest in teaching English to young learners itself. This study has also demonstrated how the participants' construction journey impacts the change of their beliefs and practices in teaching EYL. This study sheds light on the significance of the support from EYL stakeholders in affording opportunities for teachers’ learning and professional development.